A Theoretical Study of Structure and Electronic Properties of Poly (?-Caprolactone) By Density Functional Study - Hekim, Seda; Pekdemir, Mustafa Ersin (My University, 2022)
The purpose of this research is to determine the structure's electrophilic and nucleophilic character by examining at local and global chemical activity factors. The electronic behavior of Poly (?-caprolactone) was investigated by theoretical quantum chemical computation for this purpose. Natural Bonding Orbital (NBO) analysis is a powerful technique for studying stabilization energy E(2), conjugated interactions, and charge transfer in quantum chemistry molecular systems. Furthermore, dipole moment, polarizability, and hyper polarizability characteristics were used to determine the structure's nonlinear optics (Nonlinear Optical, NLO) features. All the theoretical calculations of molecular structure were calculated via the Density Functional Theory (DFT) method in the B3LYP level and STO-3G basis set.
Keywords: NBO; DFT; NLO; Poly (?-caprolactone); hardness and softness